Role of visual and non-visual opsins in blue light–induced neurodegeneration in Drosophila melanogaster - Piacenti-Silva, Marina [UNESP]; de Mattos Alves, Samuel [UNESP]; Zaparoli, Hulder Henrique [UNESP]; de Oliveira, Marcela [UNESP]; Morimoto, Juliano; Vieira, Carolina L. Zilli (Frontiers, 2025)
Light plays a key role in regulating circadian rhythms and downstream physiological and behavioural functions. However, excessive exposure to artificial blue light (450–500 nm) can disrupt sleep, metabolism and neural integrity. Visual opsins mediate light-dependent signalling, but organisms also express non-visual opsins whose roles in blue-light-induced neural stress are not well understood. We used Drosophila melanogaster knockout lines lacking either visual rhodopsin 1 (Rh11) or non-visual rhodopsin 7 (Rh71), alongside wild-type (w1118) controls. Flies were continuously exposed to 488 nm blue light (1,320 lux; 1,120 μW·cm−2) from egg deposition until they were 20 days old. DNA damage (γ-H2Av immunostaining) and vacuole formation were quantified in brain regions associated with sensory processing and neurotransmission. Rh11 flies exhibited the highest levels of DNA damage and vacuolisation compared to the w1118 and Rh71 lines. These effects were most pronounced in neuropils linked to sensory integration and synaptic activity. Our findings demonstrate that the visual opsin Rh1 plays a predominant role in blue-light-induced DNA damage and neurodegeneration in the Drosophila central nervous system. This suggests that it is visual, rather than non-visual, opsins that mediate the neurotoxic effects of exposure to artificial light.